2017
DOI: 10.3892/etm.2017.4471
|View full text |Cite
|
Sign up to set email alerts
|

Role of transient receptor potential channel 6 in the odontogenic differentiation of human dental pulp cells

Abstract: Pulp capping is a restorative technique employed in an attempt to maintain pulpal vitality and generate reparative dentin. Ca2+ released from capping materials is suggested to promote reparative dentin formation. Transient receptor potential channel 6 (TRPC6) is a receptor-operated Ca2+ channel that serves an important role in Ca2+ influx in the majority of non-excitable cells, and influences the calcium signaling and cell respond. Therefore, the purpose of the present study was to gain an insight into the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Conditioned media from tooth germ and natural dentin matrix have been used for in vitro odonto/osteoblast differentiation from stem cells [ 6 , 8 , 9 ], however, it is difficult to maintain homogenous, constant conditions when using this media. In the present study, ODM contain various combinations of ingredients, including ß-glycerophosphate, ascorbate-2-phosphate, and dexamethasone, which makes odontoblast induction easier and produce constant results [ 1 , 23 ]. Recent studies revealed that estrogen is essential for in vivo and in vitro odontogenic and osteogenic differentiation of DPSCs [ 16 , 25 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conditioned media from tooth germ and natural dentin matrix have been used for in vitro odonto/osteoblast differentiation from stem cells [ 6 , 8 , 9 ], however, it is difficult to maintain homogenous, constant conditions when using this media. In the present study, ODM contain various combinations of ingredients, including ß-glycerophosphate, ascorbate-2-phosphate, and dexamethasone, which makes odontoblast induction easier and produce constant results [ 1 , 23 ]. Recent studies revealed that estrogen is essential for in vivo and in vitro odontogenic and osteogenic differentiation of DPSCs [ 16 , 25 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data are represented by the mean ± SD of four independent experiments. Lettered subscripts indicate statistical differences between groups (p < 0.05) of ingredients, including ß-glycerophosphate, ascorbate-2-phosphate, and dexamethasone, which makes odontoblast induction easier and produce constant results [1,23]. Recent studies revealed that estrogen is essential for in vivo and in vitro odontogenic and osteogenic differentiation of DPSCs [16,25,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPC1 and TRPC6 have been reported to be expressed in odontoblasts [179,197,198]. TRPC1 plays an important role in store-operated Ca 2+ entry (SOCE) in a variety of tissues and cell types [199,200].…”
Section: Trp Channels and Their Presence In Dental Tissuesmentioning
confidence: 99%
“…TRPC6 protein expression increases with time during odontoblast differentiation from pulp tissue. Furthermore, differentiation is inhibited by downregulation of TRPC1 and TRPC6 expression, indicating involvement of these channels in the odontogenic differentiation of human dental pulp cells [197,198].…”
Section: Trp Channels and Their Presence In Dental Tissuesmentioning
confidence: 99%